Guidance for gynecologists utilizing telemedicine during COVID‐19 pandemic based on expert consensus and rapid literature reviews. Issue 3 (16th July 2020) - Grimes, Cara L.; Balk, Ethan M.; Dieter, Alexis A.; Singh, Ruchira; Wieslander, Cecilia K.; Jeppson, Peter C.; Aschkenazi, Sarit O.; Kim, Jin Hee; Truong, Mireille D.; Gupta, Ankita S.; Keltz, Julia G.; Hobson, Deslyn T.G.; et al.
Abstract: Background: COVID‐19 has impacted delivery of outpatient gynecology and shifted care toward use of telemedicine. Objective: To rapidly review literature and society guidelines and create expert consensus to provide guidance regarding management of outpatient gynecology scenarios via telemedicine. Search strategy: Searches were conducted in Medline and Cochrane databases from inception through April 15, 2020. Selection criteria: Literature searches were conducted for articles on telemedicine and abnormal uterine bleeding, chronic pelvic pain, endometriosis, vaginitis, and postoperative care. Searches were restricted to available English language publications. Data collection and analysis: Expedited literature review methodology was followed and 10 943 citations were single‐screened. Full‐text articles and relevant guidelines were reviewed and narrative summaries developed. Main results: Fifty‐one studies on the use of telemedicine in gynecology were found. Findings were reported for these studies and combined with society guidelines and expert consensus on four topics (abnormal uterine bleeding, chronic pelvic pain and endometriosis, vaginal discharge, and postoperative care). Conclusions: Guidance for treating gynecological conditions via telemedicine based on expedited literature review, review of society recommendations, and expert consensus is presented. Due to minimal evidence surrounding telemedicine and gynecology, a final consensus document is presented here that can be efficiently used in a clinical setting. Abstract : Guidance for gynecologists using telemedicine during COVID‐19 based on rapid literature review, review of society recommendations, and expert consensus in accessible format.